DARI MAHASISWA MENJADI INVESTOR: MEMAHAMI PASAR MODAL DAN INVESTASI SAHAM - Wilson Candra Teguh Pratama Pratama; Nia Nurani Nurani; Maysandra Dwianzahra Dwianzahra (ICON Publisher, 2024)
This community service activity aims to increase students' knowledge about the capital market and stock investment and encourage them to start investing. The implementation methods used include workshops, seminars, and interactive discussions involving students from the University of Muhammadiyah Gombong. Resource persons who are experienced in the investment field provide comprehensive material on capital market mechanisms, investment risks and opportunities, and smart decision-making strategies. Data analysis techniques are carried out through questionnaires filled out by participants before and after the activity, which aims to measure their level of understanding. The results of the activity showed a significant increase in student knowledge, where the average understanding score increased from 55 percent to 85 percent after participating in the socialization. In addition, 90 percent of participants expressed satisfaction with the implementation of the activity, and 85 percent planned to start investing. This activity succeeded in providing valuable insights for students and is expected to encourage them to actively participate in the world of investment.